The Rise of Cohabitation in the Southern Cone - Binstock, Georgina (2016)
This chapter analyses the increase in cohabitation in the Southern Cone (Argentina, Chile and Uruguay) and attempts to determine the extent to which consensual unions and marriages have similar traits or differ in the context of the cohabitation boom (Esteve et al. 2012). The first section of the chapter reviews the historical context of cohabitation in the Southern Cone. The second section uses census and survey data to analyse the trends in conjugal union formation in the three countries during the last 40 years. We analyse the patterns of both childbearing and union formation, as well as the differences between marriage and cohabitation based on educational attainment, labour market participation and household structure. The purpose of this analysis is to better understand whether the behaviour of married and cohabiting women with different characteristics are converging or diverging over time and tentatively, whether more egalitarian gender relationships are emerging in both types of conjugal unions.